Momentous events in the life of a cactus eaudiobook - Bowling, Dusti (Life of a Cactus, 2019)
The sequel to the critically acclaimed Insignificant Events in the Life of a Cactus follows Aven Green as she confronts yet another challenge: high school. "High School. Two words that struck fear into the heart of every armless middle schooler I knew. Which was me. And like two people online." Just as Aven starts to feel comfortable in Stagecoach Pass, with her friends and schoolmates accustomed to her lack of "armage," everything changes once again. She's about to begin high school . . . with 2,300 new kids to stare at her. And no matter how much Aven tries to play it cool, nothing prepares her for the reality. In a year filled with confusion, humiliation, fears, loss, and just maybe love, can Aven manage to stay true to herself?